Physical and Strength Properties of Paper Manufactured from Straw of Different Sudanese Sorghum Varieties - Idris, Fadl Elmoula A.; Mohammed, Nasir A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The physical and strength properties of papers manufactured from different Sudanese sorghum straws were investigated. Pulp was manufactured from straws of five different sorghum varieties namely Wad Ahmed, Hegein, Tabbat, Feterita and Hemacy. The hand sheets were produced from each variety according to the American standard and subjected to physical tests including specific volume, breaking length, tensile strength, burst index and folding endurance. The effect of beating time on these properties was also taken into accounts. The results obtained from these varieties showed that the produced papers differed from one to another according to the variety from which it was produced. It has been noticed that, the increased beating times were substantially improved the properties of paper manufactured from these straws.  For comparison purposes properties of these papers, were compared with properties of the printing paper size (A4). Although the latter was chemically treated with tilling and other improving materials, the results of comparison showed that, the paper produced from sorghum straws,  were good and very much like the standard one (A4).